2021
DOI: 10.1093/neuonc/noab002
|View full text |Cite
|
Sign up to set email alerts
|

Invasive growth associated with cold-inducible RNA-binding protein expression drives recurrence of surgically resected brain metastases

Abstract: Background Sixty percent of surgically resected brain metastases (BrM) recur within 1 year. These recurrences have long been thought to result from the dispersion of cancer cells during surgery. We tested the alternative hypothesis that invasion of cancer cells into the adjacent brain plays a significant role in local recurrence and shortened overall survival. Methods We determined the invasion pattern of 164 surgically resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…The ability of MDA-MB-231 cells to form LM upon intracranial injection was confirmed by Allen et al, who observed leptomeningeal dissemination when MDA-MB-231, but not MDA-MB-468 cells, were implanted [44]. These findings were expanded upon using a cohort of patient-derived xenograft models of brain metastases injected intracranially, which show differential propensity to form LM based upon the invasion pattern in the brain metastatic lesion (minimally versus highly invasive) and expression of CIRBP [45]. This suggests that cellular processes and molecular mediators that are present in only a subset of cancers may be involved in leading established parenchymal brain metastases to subsequently colonize the leptomeninges.…”
Section: Applying Pre-clinical Animal Models Of Lm To Study Its Undermentioning
confidence: 78%
See 1 more Smart Citation
“…The ability of MDA-MB-231 cells to form LM upon intracranial injection was confirmed by Allen et al, who observed leptomeningeal dissemination when MDA-MB-231, but not MDA-MB-468 cells, were implanted [44]. These findings were expanded upon using a cohort of patient-derived xenograft models of brain metastases injected intracranially, which show differential propensity to form LM based upon the invasion pattern in the brain metastatic lesion (minimally versus highly invasive) and expression of CIRBP [45]. This suggests that cellular processes and molecular mediators that are present in only a subset of cancers may be involved in leading established parenchymal brain metastases to subsequently colonize the leptomeninges.…”
Section: Applying Pre-clinical Animal Models Of Lm To Study Its Undermentioning
confidence: 78%
“…The converse may also be true, where leptomeningeal deposits can be observed invading into the brain parenchyma ( Figure 2). Metastatic cancer cells have been shown to cycle between the brain parenchyma and leptomeningeal compartments in rodent models [44], with cold-inducible RNA-binding protein (CIRBP) and cyclooxygenase-2 representing candidate genes implicated in this process [44,45]. It is possible that shuttling between the brain and leptomeningeal anatomical compartments is uniquely driven by invasion across the glia limitans, however, other possibilities remain.…”
Section: Defining Lm By the Route Of Entrymentioning
confidence: 99%
“…Mechanical dissociation in the operating room decreases processing time in the laboratory and aids in streamlining experimentation (Figure 2E) Dependent of the location of the brain metastasis, often a rim of the surrounding tissue within the parenchyma can be resected as well. Recent data also demonstrates heterogeneity between regions of metastatic tumors and invasion into the peritumoral border (33,34). Therefore, even with metastatic tumor regional information is routinely annotated with the tumor tissue.…”
Section: Intraoperative Considerationsmentioning
confidence: 99%
“…Compatibility with in vitro passage is not granted and efficacy has been estimated between 24% and 48.8% depending on the amount of viable cancer cells in the surgical sample, ability of the cells to form colonies in the first culture, and the degree of senescence affecting cancer cells. 24 Most brain metastatic PDX models are derived from either systemic 25 or intracranial 26 inoculation, but few models have been reported to spontaneously metastasize from orthotopic (subdermal for melanoma 21 or mammary fat-pad for breast cancer 27 ) injection. Of note, a brain-metastatic SCLC PDX model has recently been established from subcutaneous injection.…”
Section: Patient-derived Xenograft (Pdx) Modelsmentioning
confidence: 99%